(untitled) (Interdisciplinary Studies Journal, 2025)
The growing demand for innovative methodologies in the teaching of Biological Sciences has driven the adoption of strategies that promote active and meaningful learning. In this context, 3D printing stands out as a promising tool to enhance education and stimulate students’ critical and creative thinking. This technology facilitates the visualization and understanding of cellular structures, especially considering that other methods, such as the use of electron microscopes, involve high costs and limited accessibility. Additionally, it contributes to increased student engagement and interest during classes. Inserted within the framework of maker culture and active learning methodologies, this approach aims to promote pedagogical objectives through playful learning, encouraging visual and tactile interaction that sparks curiosity and student participation. This study aimed to design and 3D print the structure of a bacterium of great biological relevance, Bacillus thuringiensis (Bt), for use in workshops and Cell Biology classes at the high school level. The prototype model was developed using the free software TinkerCAD, and subsequently printed on a Flashforge 3D printer using the Fused Deposition Modeling (FDM) method, which builds objects layer by layer. As a result, a three-dimensional model of Bacillus thuringiensis was obtained, finalized with polyvinyl acetate paint from the brand Acrilex. During the process, the ideal type of filament, the most suitable printing method, infill percentage, layer height, extrusion temperature, and print speed were all defined. The printed model was used as an educational resource in Cell Biology workshops, aiding in the demonstration of bacterial morphology, physiology, and significance. Students showed interest in the activity and reported that the use of the model helped them better understand bacterial structure. It is recommended that the use of 3D printing be expanded to other topics and disciplines, as the results obtained may enrich teaching practices and improve the teaching-learning process.